Empowering Muslim Women: Bridging Islamic Law and Human Rights with Islamic Economics - Insani, Nur; Ibrahim, Zumiyati Sanu; Karimullah, Suud Sarim; Gönan, Yavuz; Sulastri, Sulastri (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
This intersectional study investigates the harmonisation of Islamic law and human rights in the context of empowering Muslim women through Islamic economics. This study applies an intersectional approach in carrying out the library research method with literature analysis carried out integratively and comprehensively to explore and review various literature sources relevant to the research topic, including journal articles, books, research reports, policy documents, and other related sources of information. The results show that harmonisation between Islamic law and human rights in empowering Muslim women through Islamic economics significantly impacts achieving gender equality and supporting sustainable development. The complexity of Muslim women's identities influenced by factors such as religion, gender, and social class demands a holistic and integrated policy approach in the economy. While the Islamic economy offers great potential to enhance the role of women as agents of change and key drivers of economic development, the incompatibility between Islamic law and human rights conventions and issues of gender inequality points to the need for more inclusive legal and policy reforms. Identifying and recognising these challenges underscores the importance of adopting a comprehensive and coordinated approach. Specific measures that need to be strengthened include inter-agency cooperation, legal and policy reforms to support better gender equality, capacity building of women in the Islamic economic sector, and raising public awareness on the importance of women's empowerment. As such, this study enriches the academic literature and offers practical guidance for policymakers, stakeholders in the Islamic economy, and the general public in advocating and implementing effective and sustainable women's empowerment.